Context as Relevance-Driven Abduction and Charitable Satisficing - Attardo, Salvatore (Frontiers in Psychology, 2016)
It has been widely assumed that the full meaning of a linguistic expression can be grasped only within a situation, the context of the utterance. There is even agreement that certain factors within the situation are particularly significant, including gestures and facial expressions of the participants, their social roles, the setting of the exchange, the objects surrounding the participants, the linguistic, cultural and educational backgrounds of the participants, their beliefs, including those concerning the situation, the social procedures and conventions that regulate the situation. Finally, there is some agreement that context is dynamic, reflexive (the speakers are mutually aware of their beliefs), not limited to linguistics actions, and last but not least, a psychological construct. This definition of context is not (very) controversial, but it leaves out two major problems, which will be addressed in this paper: how is context arrived at? And, since a perfectly natural interpretation of the above definition could be that the context of each utterance is the entire universe, how is the relevant context delimited? Four related concepts will provide the answer to both questions: abductive reasoning, driven by relevance and cooperation, and bounded rationality and the principle of charity. Simply put, context is derived abductively by the speakers assuming that for the speakers to behave the way they behave and do so rationally, a given context must be available to them. The context is bounded by the simple requirement that speakers not try to optimize their interpretation/calculation, but rather satisfice, i.e., find the first acceptable solution and by the need to follow the principle of charity, which forces intersubjective agreement. Thus abductive reasoning and bounded rationality will be shown to be sufficient to calculate the relevant context of utterances (or other rationality-driven interactions) and to effectively delimit the potentially infinite search space that must be explored to do so.